Anti-Inflammatory Activity of The Extract of Guava Leaves (Psidium guajava L) in The Rat (Rattus norvegicus L) - Weni, Linda; Harliansyah, .; Widayanti, . (Indonesian Journal of Cancer Chemoprevention, 2011)
Using of natural sources that have anti-inflammatory activity for the prevention and treatment of degenerative diseases began to be further explored. An investigation on the anti-inflammatory activity of the aqueous extract of guava leaves (Psidium guajava L.) from Sawangan, Depok on white male rats of Sprague-Dawley strain had been carried out on the carrageenan-inducedÃÂ  pawÃÂ  edemaÃÂ  method.ÃÂ ÃÂ ÃÂ  ToÃÂ  examineÃÂ  theÃÂ  effectÃÂ  ofÃÂ  guavaÃÂ  extractÃÂ  on subcutan at different doses of 125, 250 and 500 mg/kg of body weight (BW).ÃÂ  Indometacine at dose of 10 mg/kg BW was used as a positive control. Observations were made during five hours with an interval of one hour. These results demonstrate that the percentage of inflammation or edema (% E) optimal at the 4th hour and then decreased at the 5th hour, while the percentage of optimal inhibition occurred at the 5th hour. Guava extract at 125, 250 and 500 mg/kg BW reduced inhibitory percentage activities by 40.81, 55.45 and 43.61% (p<ÃÂ  0.05)ÃÂ  respectively.ÃÂ  InÃÂ  conclusion,ÃÂ  thisÃÂ  studyÃÂ  suggestsÃÂ  thatÃÂ  guavaÃÂ  extractÃÂ  hasÃÂ  anti-inflammatory properties by decreasing edema level.